2016
DOI: 10.1021/acs.jproteome.5b00864
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Francisella tularensis Gene Encoding Putative ABC Transporter Has a Pleiotropic Effect upon Production of Various Glycoconjugates

Abstract: Francisella tularensis, an intracellular pathogen causing the disease tularemia, utilizes surface glycoconjugates such as lipopolysaccharide, capsule, and capsule-like complex for its protection against inhospitable conditions of the environment. Francisella species also possess a functional glycosylation apparatus by which specific proteins are O-glycosidically modified. We here created a mutant with a nonfunctional FTS_1402 gene encoding for a putative glycan flippase and studied the consequences of its disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Therefore, we performed the serum bactericidal assay in which the wild-type, FSC200/ in dacD mutant, both complemented mutant strains, and the FSC200/ wbtDEF::Cm strain lacking LPS, were exposed to human nonimmune serum. The significant sensitivity of FSC200/ wbtDEF::Cm strain to human serum on the one hand and the resistance of FSC200 on the other hand were consistent with previously published data (Dankova et al, 2016 ). The FSC200/ in dacD mutant strain also exhibited some degree of sensitivity to complement-mediated lysis.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, we performed the serum bactericidal assay in which the wild-type, FSC200/ in dacD mutant, both complemented mutant strains, and the FSC200/ wbtDEF::Cm strain lacking LPS, were exposed to human nonimmune serum. The significant sensitivity of FSC200/ wbtDEF::Cm strain to human serum on the one hand and the resistance of FSC200 on the other hand were consistent with previously published data (Dankova et al, 2016 ). The FSC200/ in dacD mutant strain also exhibited some degree of sensitivity to complement-mediated lysis.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, the mutation of wbtC gene from LPS biosynthetic locus resulted in not only altered LPS but also reduced protein glycosylation [66]. Similarly the mutation of the putative glycan flippase gene FTS_1402 in the FCS200 strain lead to alteration in protein glycosylation and also a decrease in LPS production [65], suggesting a cross-talk between LPS biosynthesis and protein glycosylation in F.…”
Section: Ost-mediated Protein O-glycosylation In Gram-negative Bacteriamentioning
confidence: 99%
“…The OST involved in the en bloc glycosylation was identified as PglA (encoded by FTL_0425 in FCS200 strain, and FTT_0905 in SchuS4 strain) [36]. The 12.5 kB gene cluster FTT0789-FTT0800 in the SchuS4 strain was shown to be involved in the assembly and translocation of the hexasaccharide [64,65]. Interestingly, the mutation of wbtC gene from LPS biosynthetic locus resulted in not only altered LPS but also reduced protein glycosylation [66].…”
Section: Ost-mediated Protein O-glycosylation In Gram-negative Bacteriamentioning
confidence: 99%
“…OSTs substrates are lipid-linked oligosaccharides while the GTs substrates are usually nucleotide-activated sugars. It was only very recently (Dankova et al, 2016) that the glycosylation machinery of Francisella was found to involve a variety of sugar biogenesis enzymes, glycosyltransferases, a flippase, and a protein-targeting oligosaccharyltransferase. As both type A and type B strains of F. tularensis subspecies expressed an O -linked protein glycosylation system, which utilizes core biosynthetic and assembly pathways, O -linked protein glycosylation may be a feature common to members of the Francisella genus (Egge-Jacobsen et al, 2011).…”
Section: Pathogen Point Of Viewmentioning
confidence: 99%
“…This protein is part of a gene cluster, which is thought to encode a polysaccharide additional to the lipopolysaccharide O antigen. Another protein, encoded by FTS_1402 , was found to be involved in glycoprotein synthesis and to also contribute in part to LPS/capsule and/or Capsule Like Complex (CLC) production (Dankova et al, 2016). The resulting FTS_1402 mutant presented more sensitivity to serum complement.…”
Section: Pathogen Point Of Viewmentioning
confidence: 99%